2018
DOI: 10.1002/mar.21078
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and consequences of chronic impulsive buying: Can impulsive buying be understood as dysfunctional self‐regulation?

Abstract: Researchers reach different conclusions about the functional or dysfunctional nature of impulsive buying behavior. While many note the use of impulsive buying as a form of mood regulation, there is disagreement about whether this is functional or dysfunctional and the extent to which it causes financial harm. This paper draws on data from a U.K. national survey sample (N = 109,472) to contribute to these debates. Study results suggest that impulsive buying is more common for those who have most need to regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 49 publications
1
61
1
4
Order By: Relevance
“…The association of neuroticism with impulsive buying could explain the popular concept of “retail therapy” where shopping is understood as means of mood repair and enhancement and is consistent with “mood repair” explanations of impulsive buying (e.g. Atalay & Meloy, ; Fenton‐O'Creevy et al, ).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…The association of neuroticism with impulsive buying could explain the popular concept of “retail therapy” where shopping is understood as means of mood repair and enhancement and is consistent with “mood repair” explanations of impulsive buying (e.g. Atalay & Meloy, ; Fenton‐O'Creevy et al, ).…”
Section: Discussionmentioning
confidence: 76%
“…Many studies that have looked at individual difference correlates of impulsive buying (IB) have concentrated on dysfunctional emotional regulation or prevention and promotion focus. For example, Fenton‐O'Creevy et al () showed that Behavioral Inhibition and Activation (BIS/BAS) was logically and significantly related to IB. Some studies have attended to specific personality correlates of IB.…”
Section: Personality Correlatesmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that mental simulation was a categorical variable; it could not directly enter the regression equation, so we needed to convert it into dummy variables first. In addition, because of the unbalanced gender ratio (females accounted for 82% of all participants) in our study and the gender differences in impulsive buying reported in previous studies,31 we controlled gender to avoid its extraneous effects on the dependent variable. We used 1000 bootstrap samples, and biases were corrected at 95% confidence intervals (CI) to calculate the effect of each variable.…”
Section: Methodsmentioning
confidence: 99%